Dampak Perubahan Iklim Global Terhadap Parameter Oseanografi: Ancaman bagi Ekosistem Laut dan Kehidupan Pesisir di Maluku - Pelu, Fadli (CV. SINAR HOWUHOWU, 2025)
This research was conducted to examine the impact of global climate change on oceanographic parameters and its threats to marine ecosystems and coastal life in the Maluku region. The study was carried out through a literature review, utilizing scientific publications indexed in several databases such as Google Scholar, Sinta, DOAJ, and Scopus. The findings indicate that climate change has an effect on rising sea temperatures and sea level rise, which causes marine ecosystems, such as coral reefs, to bleach and leads to a decline in fish catch yields. Other findings show that other oceanographic parameters, such as pH, water currents, and other elements, also change due to global warming. The livelihoods of local communities are affected by the loss of land area caused by rising sea levels.